The methylic versus the ethylic route: considerations about the sustainability of Brazilian biodiesel production - Leoneti, Alexandre Bevilacqua; Aragão-Leoneti, Valquiria [UNESP]; Galina, Simone Vasconcelos Ribeiro; Porto, Geciane Silveira (Springer Nature, 2017)
Brazil is considered one of the world’s leading producers of biofuels given the predominance of ethanol fuel in its energy matrix. However, despite the prominence of Brazil in ethanol production, the vast majority of biodiesel production plants in Brazil use methanol instead of ethanol as the alcohol for transesterification reaction, as is generally the case in the rest of the world. The aim of this paper is therefore to examine the transesterification process in the Brazilian biodiesel production in terms of sustainability. In this regard, it was necessary to evaluate the way in which the industrial process is currently carried out, the role of government incentives or subsidies for the use of ethanol to produce biodiesel, and the investments of companies in technology development for the same purpose. This study presents indications that the development of the biodiesel market in Brazil is still oriented toward a production model which is inconsistent with the environmental and social aspects of sustainability.
Keywords: Biodiesel; Ethanol; Methanol; Transesterification